Redrawing the Planners' Circle: Analyzing Trip-Level Walk Distances Across Two National Surveys. Issue 4 (2nd October 2021) - Merlin, Louis A.; Teoman, Denis; Viola, Marco; Vaughn, Hailey; Buehler, Ralph
Abstract: Problem, research strategy, and findings: For decades, planners have been drawing circles of a quarter-mile radius to determine easily walkable distances for neighborhood and activity center planning. However, the radius of such "planners' circles, " or walksheds, is often informed more by convention than by data. Here we examine walk-trip distances based on two national household travel surveys for the United States and Germany. We describe how walk distances vary by personal and trip characteristics, with a particular focus on trip purpose and pedestrian age. We conducted both univariate and multivariate analyses to compare patterns between the United States and Germany. The multivariate analysis examines quantile regressions for 50th, 75th, and 90th percentiles to understand both typical and longer walk distances. The observed distances that people walk vary significantly across age groups, trip purposes, and national contexts. Leisure trips tend to be longest, whereas shopping and errand trips tend to be shortest. There are substantial differences between the United States and Germany in the average lengths of walks (mean/median walk distance: Germany, 1, 490/980 m, 0.93/0.61 miles; United States, 970/530 m, 0.60/0.33 miles) and in the effects of independent variables. A significant portion of the variation in walk-trip distances between the United States and Germany is likely due to Germany's higher quality walk environments. Takeaway for practice: Rather than always resort to a quarter-mile or 400-m radius, planners can use the data here to customize the size of the planners' circle, or walkshed, they draw to take into account the primary trip purposes and demographic segments under consideration. Moreover, planners can draw circles with a shorter radius corresponding to the 50th percentile to plan for the most common walk-trip lengths while also considering larger circles corresponding to the 75th and 90th percentiles to provide more supportive and safer pedestrian environments for longer trips.